Growth Pattern and Reproductive Biology of the Mudskipper (Boleophthalmus boddarti) in the Maro River Area, Semangga District, Merauke Regency - Nova Permaeta Hartanty; Sunarni; Dandi Saleky (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aimed to analyze the growth and reproductive patterns of the mudskipper (Boleophthalmus boddarti) in the Maro River area, Semangga District, Merauke Regency. The study was conducted in the Maro River area, Semangga District, Merauke Regency, from August to October 2024. Sampling was carried out twice per month using a purposive sampling technique. Quantitative data analysis was applied to evaluate growth patterns and reproductive characteristics, including sex ratio and gonadal maturity stage (GMS), of the mudskipper (Boleophthalmus boddarti). The results showed that a total of 56 mudskippers were collected during the study, consisting of 20 males and 36 females. The growth pattern analysis yielded the equation W = 0.0018L3.5138 in Sidomulyo Village and W = 0.0015L3.5831 in Urumb Village, indicating a positive allometric growth pattern. In terms of reproduction, the sex ratio of the mudskipper population remained relatively balanced. Regarding gonadal maturity stage, males were found only at GMS I, whereas females were recorded at GMS I and GMS II.